2015
DOI: 10.5935/0004-2749.20150074
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and clinical implications of choroidal thickness in patients with inflammatory bowel disease

Abstract: Approved by the following research ethics committee: Gazi University Ethics Committee. Number N o 53 -26/01/2015. ABSTRACTPurpose: Ocular inflammation is a frequent extraintestinal manifestation of inflammatory bowel disease (IBD) and may parallel disease activity. In this study, we evaluated the utility of a choroidal thickness measurement in assessing IBD activity. Methods: A total of 62 eyes of 31 patients with IBD [Crohn's disease (CD), n=10 and ulcerative colitis (UC), n=21] and 104 eyes of 52 healthy blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Önal at al. declared a similar study which CT was increased in IBD with ileal involment (8). Similarly we find out increased CT in both Crohn and UC patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Önal at al. declared a similar study which CT was increased in IBD with ileal involment (8). Similarly we find out increased CT in both Crohn and UC patients in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation of the eye affects the choroidal vascular structure. Some authors reported many ocular inflammatory diseases that affect the choroid like Vogt–Koyonagi–Harada (VKH), sarcoidosis, Behçet's disease, inflammatory bowel disease, and posterior scleritis before [ 19 22 ]. According to these different studies in the acute phase, choroidal thickness usually increases, but recurrent inflammatory changes decrease the CT and causes the atrophic changes which results as choroidal thinning.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that inflammation could be the reason [18]. However, Onal et al [19] reported no significant difference of the choroidal thickness between the patients with inflammatory bowel disorder and control individuals. It has been shown that the inflammatory process related to disease duration in psoriasis also affects the choroidal thickness [20,21].…”
Section: Optical Coherence Tomography Is a Non-invasivementioning
confidence: 99%
“…It has been shown that the inflammatory process related to disease duration in psoriasis also affects the choroidal thickness [20,21]. Consequently, there are many disorders that have effects on choroidal structure and they may indirectly contribute the pathogenesis of chorioretinal diseases [14][15][16][17][18][19][20][21][22][23]. The AMD prevalence is lower in rheumatoid arthritis patients who receive anti-inflammatory treatment [24].…”
Section: Optical Coherence Tomography Is a Non-invasivementioning
confidence: 99%